Evaluation of tumor-infiltrating lymphocytes and molecular alterations in advanced colorectal carcinoma: a retrospective study in Southern Brazil - Gabriela Remonatto; Emily Ferreira Salles Pilar; Fernanda De-Paris; Pedro Guilherme Schaefer; Lúcia Maria Kliemann (Surgical and Experimental Pathology)
Abstract Background Colorectal carcinoma (CRC) is a leading cause of cancer-related deaths globally, ranking second in mortality rates. Cancer progression is influenced not only by genetic mutations in tumour cells but also by the surrounding tumour microenvironment, which can promote tumour growth or dampen the host’s immune response. Microsatellite instability tumours often exhibit a high presence of tumour-infiltrating lymphocytes (TILs), including cytotoxic T cells. TILs are increasingly recognised as important biomarkers across various cancer types, and the mismatch repair (MMR) status is particularly relevant in determining patient eligibility for immunotherapy, especially with immune checkpoint inhibitors in advanced disease. In the present study, we evaluated the presence and intensity of lymphocytic infiltrate in patients with advanced CRC at a tertiary hospital in southern Brazil. Methods A cross-sectional retrospective study was conducted to analyse the presence and intensity of TILs and their association with clinical data, as well as alterations in KRAS, NRAS, BRAF, NTRK, and MMR. Results Analysis of the presence and intensity of TILs in 241 tumours revealed that 70 (29.1%) were TIL + and 171 (70.9%) were TIL−. Only one tumour was NTRK+; this tumour was in a female patient, located in the right colon, TIL−, and deficient in MLH1/PMS2. There were no significant differences in the associations between the presence and intensity of the infiltrate and the clinical characteristics and molecular alterations studied. Conclusions The data from our study differed from those reported in the literature in that we found no association between a higher frequency and intensity of TILs and MMR deficiency. Associations with the molecular profiles of the KRAS, NRAS, and BRAF genes also showed no statistically significant differences.